Peran Guru Kristen Sebagai Pembimbing Siswa terhadap Dekadensi Etika Digital - Giawa, Greys July Sonatha; Dwikristanto, Yanuard Putro (Diligentia: Journal of Theology and Christian Education, 2025)
The rapid advancement of digital technology has profoundly impacted social interactions and individual behaviours, particularly among students who increasingly disregard traditional social norms, contributing to a significant decline in digital ethics. This research, employing a literature review methodology, critically examines the transformative role that Christian education can play in restoring digital ethics among young people. It highlights the crucial function of Christian teachers, who are envisioned not just as educators but as mentors guiding students towards Christ’s redemption. The aim is to teach students to respond ethically in their digital interactions as a reflection of their redemption. The findings suggest that teachers who are deeply committed to Christ and who recognize that students, though marred by sin, are still made in the image of God, can effectively nurture ethical behaviour. This study emphasizes the vital importance of integrating Biblical truths as the foundational framework for ethical education in the digital age, proposing that such integration can equip students to navigate the complex ethical landscapes of modern digital environments. BAHASA INDONESIA ABSTRACT Kemajuan pesat teknologi digital telah memberikan dampak yang mendalam terhadap interaksi sosial dan perilaku individu, khususnya di kalangan siswa yang semakin mengabaikan norma sosial tradisional, sehingga berkontribusi pada penurunan etika digital yang signifikan. Penelitian ini, dengan menggunakan metode kajian pustaka, secara kritis mengkaji peran transformatif yang dapat dimainkan oleh pendidikan Kristen dalam memulihkan etika digital di kalangan generasi muda. Penelitian ini menyoroti peran penting guru Kristen, yang tidak hanya dipandang sebagai pendidik, tetapi juga sebagai pembimbing yang menuntun siswa menuju penebusan dalam Kristus. Tujuannya adalah untuk mengajarkan siswa agar mampu merespons secara etis dalam interaksi digital mereka sebagai wujud dari pengalaman penebusan tersebut. Temuan penelitian menunjukkan bahwa guru yang memiliki komitmen mendalam kepada Kristus, dan yang menyadari bahwa siswa, meskipun telah rusak oleh dosa, masih mencerminkan gambar dan rupa Allah, dapat secara efektif menumbuhkan perilaku etis. Studi ini menekankan pentingnya mengintegrasikan kebenaran Alkitab sebagai kerangka dasar dalam pendidikan etika di era digital, dengan mengusulkan bahwa integrasi semacam ini dapat membekali siswa untuk menghadapi lanskap etika yang kompleks dalam lingkungan digital modern.